Bednarz i Frasyniuk - ulotka nr 5 . Bednarz and Frasyniuk - flier no. 5 - Agencja Informacyjna Solidarności Walczącej. (Agencja Informacyjna Solidarności Walczącej, 1983)
Double-sided, b&w print on white paper. The leaflet informs about the circumstances of the hunger strike of Piotr Bednarz and Władysław Frasyniuk in the Barczew prison and appeals for protests in their support.